Prenatal risk score in high risk pregnancy cases and perinatal outcome: a study from South India - Bansal, Pooja; Verma, Deepika; Bansal, Akhil; Verma, Abhyuday (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Identification of a high risk pregnancy by Coopland score helps the obstetrician to identify patient at high risk and also elaborate a prognosis of pregnancy. The present study was conducted to evaluate perinatal outcomes in high and low risk pregnancies. Methods: In the present study of 100 cases of high risk caesarean section were evaluated and compared with 100 cases of low risk caesarean sections over a period of two years. Results: 40% and 28% of the high risk and low risk group respectively had low birth weight baby. In the high risk group, 2% had neonatal death, while these figures were 0% in the control group respectively. 28% babies in the study group and 18% babies in the control group had mild to severe depression and Apgar score below 6-4. 42% and 12% babies in the high risk and low risk group respectively had perinatal morbidity which was in the form of prematurity, IUGR, respiratory distress syndrome and birth asphyxia. 7% and 4% cases in both study and control group respectively had poor perinatal outcome. Conclusions: We suggest Coopland risk scoring for every case admitted for a caesarean section, which will be definitely helpful in predicting and evaluating the eventual perinatal outcomes. Appropriate timely care and referral can have a positive impact in lowering the perinatal mortality and morbidity and possibly better maternal outcome.